Effect of 5-fluorouracil on Pseudomonas aeruginosa: impact on virulence, biofilm formation, and bacterial growth - Niazy, Amani A.; Alrashed, May M.; Niazy, Abdurahman A. (Frontiers in Microbiology, 2025)
Pseudomonas aeruginosa is a Gram-negative opportunistic pathogen that poses a significant threat to public health due to its inherent and acquired resistance to multiple antibiotics. This mini-review explores the antimicrobial potential of 5-fluorouracil (5-FU), a chemotherapeutic agent normally used in oncology, and currently under investigation for its bacteriostatic and antibiofilm effects against P. aeruginosa. 5-FU functions by inhibiting thymidylate synthase, disrupting nucleotide metabolism, and interfering with essential bacterial processes, such as quorum sensing. Studies in vitro have demonstrated its ability to inhibit biofilm creation and decrease virulence, but findings about its impact on preformed biofilms have been contradictory. Synergistic interactions between 5-FU and antibiotics, especially gentamicin, have shown promise in enhancing antibacterial effectiveness. The aim of this mini-review was to consolidate current findings, pinpoint research gaps, and suggest future directions for potentially repurposing 5-FU as an adjunctive treatment for P. aeruginosa. By placing the current evidence in context, we hope to guide further studies toward determining the clinical viability of 5-FU as a treatment option against this formidable pathogen.